Zhuang Food Culture: Meaning and Representation in the Process of New Media Communication in China - Yanyan, Chen; Phanlukthao, Peera (Journal of Ecohumanism, 2024)
Designing a qualitative research method using observations, in-depth interviews, group discussions, and literature review data fieldwork survey collection investigated by participants to the meaning and representation of Zhuang food culture in the process of new media communication in China. The Zhuang people are a Tai-speaking ethnic group, mostly living in the Guangxi Zhuang Autonomous Region in Southern China. Food also plays a critical role in symbolizing happiness in Chinese culture. Zhuang food culture holds seven tiers of meaning for the Zhuang people, manifested in both traditional festivals and daily life. In Chinese culture, verbal communication is most accurately interpreted in the context of nonverbal communication, social hierarchy, and other background information. Social roles and a concern for respect and harmony inevitably have a bearing on communication. Zhuang food culture reveals that amidst the development of new media communication in China. Focuses on the Zhuang Sanyuesan Festival activities: A deeper understanding of the unique cultural characteristics of this ethnic group in new media communication; the Five-Color Sticky Rice; the Zhuang society and the outside world continuously are developing increasingly; the transformation of the Zhuang people through their production and life practices; etc., The representation of Zhuang food culture on new media platforms is primarily conducted through three dimensions: food culture, regional culture, and traditional Zhuang culture. Zhuang Food Culture has the remarkable ability to bring people together and create a sense of connection. For instance, dumplings, with their round shape and plump filling, symbolize wealth and prosperity and are often eaten during the Chinese New Year to usher in a prosperous year ahead.